A narrative evaluation of a community‐based nurse navigation role in an urban at‐risk community. (29th June 2017) - Feather, Janice; Carter, Nancy; Valaitis, Ruta; Kirkpatrick, Helen
Abstract: Aims: To explore community members' stories of their experiences with a Nurse Navigator programme serving an urban neighbourhood and primary care practice to address persistent health and social barriers adversely affecting health equity and well‐being. Background: In response to striking health and social inequalities existing across neighbourhoods in a large southern city in Ontario, Canada, a pilot programme was designed to improve health and social outcomes in a specific "at‐risk" neighbourhood. The programme includes nurse‐led navigation support for individuals and families and networking to facilitate improved service integration at a systems level. Design: A narrative inquiry approach based on the Three‐Dimensional Narrative Inquiry Space method, as described by Clandinin & Connelly ( Narrative inquiry: Experience and story in qualitative research, 2000 ). Methods: A thematic analysis of nine community members' life stories from narrative semi‐structured interviews (January–June 2014) in conjunction with field notes, observations and documents. Participants' life stories created a common narrative of the experience of navigation in a community setting. Findings: There were four main themes: "opening the door"; "more than just a conversation"; "making connections"; and "on a new trajectory". Participants valued the development of a therapeutic relationship, which optimized social inclusion, barrier reduction and connectivity to supportive health and social services. Conclusions: The relational process of navigation as an antecedent to barrier reduction has direct implications for programme development, continuing education of navigators and quality improvement of existing navigation services. Study findings have implications for development of navigation competencies for nurses working with priority populations to address health inequities.